Variability of fruit characters in kokum (Garcinia indica Choisy) - Haldankar, V N Kore, S R Nimbalkar, P M (Journal of Spices and Aromatic Crops, 2005)
The fruit characters of 22 genotypes of kokum (Garcinia indica) were studied at Dapoli (Maharashtra). The genotypes exhibited significant variation for all the fruit characters and the environmental coefficient of variation recorded for all the fruit characters was very low. The higher magnitudes of phenotypic and genotypic coefficient of variations indicated good amount of variation among the genotypes. Estimates of heritability and genetic advance were relatively higher for length, weight and volume of fruit, fresh rind weight, pulp weight and dry seed weight. The genotypes K-29, K-32, K-1 46, KN-1, KN-3, KN-4 and KN-5 were pronlising.